Modelagem da precificação de imóveis rurais no estado do Ceará, Brasil - Assis Júnior, José Otacílio de (2023)
Pricing rural properties is a very delicate task, as setting the price of a property involves several factors that influence its market value. Furthermore, it is an activity that is still little explored from a multivariate point of view, the way in which the variable availability of water resources influences the value of land is ignored and there is a need to understand a hierarchy of factors that most explain the value of bare land. From this perspective, the thesis work was divided into two chapters: “Hydrological influence on the pricing of rural properties in the Brazilian semi-arid region: the case of the state of Ceará” and the second “Effect of the operation of non-strategic reservoirs, for irrigation, on the valuation of rural properties: The case of the Oriente / Forquilha farm – Ceará”. The data used in this study are official and secondary, coming from price research carried out by the National Institute of Colonization and Agrarian Reform – INCRA in 2020. The first chapter aimed to identify how the variables: land use typology, irrigation potential, precipitation, type of exploration, location of the property and size of the property influence the formation of the price of rural land in the State of Ceará and a model was generated to estimate the value of bare land. From the results, it was clear that the analysis of the variables that influence the price of a rural property must be carried out taking into account the interaction with other variables and that for the State of Ceará, the irrigation potential is a fundamental factor for appreciation of rural properties and is directly associated with the best soils and the practice of agriculture. Furthermore, the estimated multivariate model was tested using 123 properties of different types, and always obtained values above 75% of the properties tested within the confidence interval. In the second, the objective was to understand how the water availability used for irrigation by the NeStRes model is a variable that can be important for the appreciation of rural properties and forage production. A case study was carried out at Fazenda Oriente with an area of 600 ha, located in the municipality of Forquilha – CE, in a caatinga region in the semi-arid region of Northeastern Brazil, characterized by average precipitation much lower than potential evapotranspiration. It was concluded that: just the presence of a dam is not enough to increase the value of a rural property; there is agronomic and economic viability for irrigation using the NeStRes model; and Fazenda Oriente increases in value if irrigation is used. The work brought contributions with relevant information on the variables that directly influence the price of rural properties in the state of Ceará, which could serve as support for different market agents (individuals, banking institutions and public entities) for decision-making at the time of transact a rural property.